2020
DOI: 10.29244/jmo.v11i2.30650
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Bauran Promosi dan Destinasi Wisata terhadap Keputusan Berkunjung pada Wisata Taman Nasional Baluran

Abstract: Baluran National Park is one of the Indonesian interesting tour destinations to be visited by local and foreign tourists which is located in Situbondo, East Java. Promotion and condition of tourist destination components are needed to attract visitors. This research aimed to determine the effect of the promotion mix and tourist destination components on the decision to visit Baluran National Park. Primary data was taken by observation, interview with managers and also offline and online surveys. Purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…That is, the sales promotion has been done well by the manager of Papuma Beach so that it can influ-ence the level of tourist decision making in choosing Papuma Beach as a tourist attraction to be visited. This finding supports the results of previous studies [3][5] [9]. Based on the description of respondents' answers, the sales promotion variable shows two indicators are in the good category.…”
Section: Hypothesissupporting
confidence: 90%
See 4 more Smart Citations
“…That is, the sales promotion has been done well by the manager of Papuma Beach so that it can influ-ence the level of tourist decision making in choosing Papuma Beach as a tourist attraction to be visited. This finding supports the results of previous studies [3][5] [9]. Based on the description of respondents' answers, the sales promotion variable shows two indicators are in the good category.…”
Section: Hypothesissupporting
confidence: 90%
“…In particular, there are differences in the use of indicators to measure advertising and tourist visiting decisions variables so that they can give different results. However, this study is in line with Andrianto & Masruroh [9] and Subagja et al [12]. Several studies outside the topic of tourism have also found that advertising has no effect on purchasing decisions [13][14] [15][16][17].…”
Section: Hypothesissupporting
confidence: 89%
See 3 more Smart Citations